Pengelompokan Pegawai di Badan Pengembangan Sumber Daya Manusia Provinsi Sumatera Utara Berdasarkan Usia, Tingkat Pendidikan dan Golongan Menggunakan Metode K-Means Clustering - Elma Dwi Ariana Aprilia Zam; Dwi Haprida Ningsih; Muhammad Arfie Munawar; Rivani Kabrina Br Surbakti; Riri Syafitri Lubis (FKIP, Universitas Palangka Raya, 2025)
This study aims to classify employees at the North Sumatra Provincial Human Resources Development Agency (BPSDM) based on age, education level, and rank using the K-Means Clustering method. Age, education level (converted to numeric), and rank (converted to numeric) data were processed through preprocessing, cluster number determination, K-Means implementation, and evaluation stages. The results showed that employees were grouped into three clusters: 1) dominated by ages 54-64 years, S2 education, rank IV/d; 2) dominated by ages 43-53 years, S2 education, rank III/d; 3) dominated by ages 32-42 years, SLTA education, rank III/b. This classification provides employee characteristic information to support human resource management.